2020
DOI: 10.1523/jneurosci.0221-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

A Minimal Biophysical Model of Neocortical Pyramidal Cells: Implications for Frontal Cortex Microcircuitry and Field Potential Generation

Abstract: Ca 21 spikes initiated in the distal trunk of layer 5 pyramidal cells (PCs) underlie nonlinear dynamic changes in the gain of cellular response, critical for top-down control of cortical processing. Detailed models with many compartments and dozens of ionic channels can account for this Ca 21 spike-dependent gain and associated critical frequency. However, current models do not account for all known Ca 21 -dependent features. Previous attempts to include more features have required increasing complexity, limit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 115 publications
(227 reference statements)
0
17
1
Order By: Relevance
“…LFP β-bursts were most prominent in the upper cortical layers but were not synchronized across the cortical column. Although SEF exhibits the functional, biophysical, and anatomical properties required to contribute to EEG signals (Sajad et al 2019(Sajad et al , 2022Herrera et al 2020), we found no evidence that EEG β-bursts could be caused by LFP β-bursts. These findings challenge a prevailing hypothesis and constrain models of the functional microcircuitry of β-burst generation during cognitive control.…”
Section: Introductioncontrasting
confidence: 78%
See 1 more Smart Citation
“…LFP β-bursts were most prominent in the upper cortical layers but were not synchronized across the cortical column. Although SEF exhibits the functional, biophysical, and anatomical properties required to contribute to EEG signals (Sajad et al 2019(Sajad et al , 2022Herrera et al 2020), we found no evidence that EEG β-bursts could be caused by LFP β-bursts. These findings challenge a prevailing hypothesis and constrain models of the functional microcircuitry of β-burst generation during cognitive control.…”
Section: Introductioncontrasting
confidence: 78%
“…Although the relationship between intracortical LFP and EEG signals is uncertain, we know that EEG signals measured over the scalp are generated by microcircuits within the cortex (e.g., Herrera et al 2020;2022) such that associations between the activity of particular neurons and EEG signatures can be observed (e.g., Sajad et al 2019Sajad et al , 2022. Biophysical modeling has suggested that cortical β-.…”
Section: Introductionmentioning
confidence: 99%
“…The current dipole moment is assumed to originate from postsynaptic currents caused mainly by the activation of pyramidal cells perpendicular to the cortical surface (Hämäläinen et al, 1993) and from nonlinear processes taking place in their dendrites (Herrera et al, 2020; Suzuki and Larkum, 2017). Therefore, we can write as , with and representing its orientation and time-varying amplitude, respectively (Riera et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…To compare the estimated EEG derived from these two approaches, we calculated the resulting EEG (ground-truth EEG) directly mapping the transmembrane currents into the scalp potentials described previously (Herrera et al, 2020). We quantified the mismatch error of each dipolar approach by calculating the magnitude (MAG) and the relative difference (RDM) measures (Meijs et al, 1989) between them and the ground-truth EEG at 15 randomly selected positions, designated as the center of the cortical column, throughout the monkey brain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation